ELECTROCHEMICAL STUDIES FOR CORROSION INHIBITION OF MILD STEEL BY CHRYSOPHYLLUM ALBIDUM EXTRACT - Chigozie, Akoma; Eziaku, Osarolube; O. E., Abumere (International Journal of Research -GRANTHAALAYAH, 2018)
The corrosion behavior of mild steel in carbonated drinks produced by Nigerian Breweries (Fanta, Sprite and Coke) was studied in the presence and absence of an eco-friendly inhibitor, Chrysophyllum albidum using Potentiodynamic polarization technique at 25 °C. Results showed that Chrysophyllum albidum reduced the current density (icorr), which in turn means that the corrosion rate was reduced significantly. The inhibition efficiency was found to be 93%, 78.6% and 87.5% for Fanta, Sprite and Coke respectively. The study also showed that Chrysophyllum albidum functioned as a mixed-type corrosion inhibitor in the three environments studied and therefore presents it as a long-term inhibitor for the corrosion of mild steel.